1989
DOI: 10.1039/dt9890002077
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear copper(II) complexes of new dinucleating ligands with a pyrazolate group as an endogenous bridge. Effects of exogenous azide and acetate bridges on magnetic properties

Abstract: N e w dinucleating ligands containing pyrazole as an endogenous bridging group, 3,5-bis-[N-(2-pyridylmethyl)carbamoyl] pyrazole ( H3L1), 3,5-bis{N-[2-(diethylamino)ethyl]carbamoyl}pyrazole ( H3L2), and 3,5-bis{N-[3-(dimethylamino)propyl]carbamoyl}pyrazole ( H3L3), and their binuclear copper(i1) complexes with azide or acetate ion as an exogenous bridge, [Cu,L(N,) (H,O),]-H,O (L = L1--L3) and [Cu,L1 (02CMe)]-2MeOH, have been obtained. Cryomagnetic investigations (5-300 K) reveal a significant antiferromagnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 3 publications
1
17
0
1
Order By: Relevance
“…[5,6] Further control of the metalϪmetal separation, as well as of the steric and electronic properties of the individual metal ions, can be achieved by appropriate chelating side arms attached to the 3-and 5-positions of the heterocycle, [7,8] usually giving rise to either bis(µ-pyrazolato) bridged species L 2 M 2 (A, Scheme 1) [9][10][11][12][13][14][15] or LM 2 X complexes featuring secondary bridges within the dimetallic pocket (B). [16][17][18][19][20][21][22][23][24] [a] Institut für Anorganische Chemie der Georg-AugustUniversität Göttingen Tammannstraße 4, 37077 Göttingen, Germany Fax: (internat.) ϩ 49-(0)551-393063 E-mail: franc.meyer@chemie.uni-goettingen.de [b] Anorganisch-Chemisches Institut der Universität Heidelberg Im Neuenheimer Feld 270, 69120 Heidelberg, Germany [ ‡] New address: Crompton GmbH, Ernst-Schering-Straße 14, 59192 Bergkamen, Germany close proximity to the low-spin nickel(II) center.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Further control of the metalϪmetal separation, as well as of the steric and electronic properties of the individual metal ions, can be achieved by appropriate chelating side arms attached to the 3-and 5-positions of the heterocycle, [7,8] usually giving rise to either bis(µ-pyrazolato) bridged species L 2 M 2 (A, Scheme 1) [9][10][11][12][13][14][15] or LM 2 X complexes featuring secondary bridges within the dimetallic pocket (B). [16][17][18][19][20][21][22][23][24] [a] Institut für Anorganische Chemie der Georg-AugustUniversität Göttingen Tammannstraße 4, 37077 Göttingen, Germany Fax: (internat.) ϩ 49-(0)551-393063 E-mail: franc.meyer@chemie.uni-goettingen.de [b] Anorganisch-Chemisches Institut der Universität Heidelberg Im Neuenheimer Feld 270, 69120 Heidelberg, Germany [ ‡] New address: Crompton GmbH, Ernst-Schering-Straße 14, 59192 Bergkamen, Germany close proximity to the low-spin nickel(II) center.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, below 18 K, the dominant phenomenon is one of intermolecular antiferromagnetic interactions and/or zero-field splitting effects in the ground state. The magnetic analysis was carried out by using the theoretical expression of the magnetic susceptibility deduced from the Heisenberg spin Hamiltonian: H ¼ À2JŜ 1Ŝ2 À DŜ z and v M is given by [29] …”
Section: Uv-vis Spectrummentioning
confidence: 99%
“…The orbital orthogonality found in such PBA analogues, however, requires the linearly aligned metal-ligand-metal structures, as well as the specific combination of metal ions such as Cr(III)/Cr(II), so that it is considered to have less degrees of freedom in molecular structures. On the other hand, it has been known that some heterogeneous bridging ligands between two Cu(II) ions make different contributions to the magnetic exchange interactions [9,10]. A pyrazole, which is a heterocyclic five-membered ring compound, is often used as a bridging ligand between two metal ions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been known that some heterogeneous bridging ligands between two Cu(II) ions make different contributions to the magnetic exchange interactions [9,10]. A pyrazole, which is a heterocyclic five-membered ring compound, is often used as a bridging ligand between two metal ions [9][10][11][12]. Kida, Okawa, and co-workers reported that pyrazole-bridged dinuclear-Cu(II) complexes with azide and acetate as counter bridging-ligands shown in Figure 1 exhibit anti-ferromagnetic (AFM) and ferromagnetic (FM) behavior, respectively [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation